Review and clinal variation of New Zealand Anabaxis Raffray (Coleoptera: Staphylinidae: Pselaphinae: Goniaceritae) - Shen, Jia-Wei; Leschen, Richard A. B. (Zootaxa, 2018)
The New Zealand members of the genus Anabaxis Raffray are revised to accommodate three species, including one new species: Anabaxis chathamensis sp. nov. A key and an illustrated catalogue to the described species from New Zealand and Australia are included. Lectotypes are designated for A. brevis Oke, A. electrica King, A. foveolata Broun, A. inusitata Blackburn, A. lunatica King, A. quinquefoveolata Raffray, and A. vagus Oke. The widespread New Zealand species A. foveolata exhibits an unusual form of clinal variation in sex-linked characters of the male legs. The length of the tibial spine increased with increasing latitude and the length of the mesotrochanteral spine decreased with increasing latitude.